Marketing Strategy for Halal And Healthy Products in Increasing Consumer Purchase Intention (A Case Study on Mie Muhammadiyah) - Iswahyuni. S, Zalsa; Sholahuddin, muhammad (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This study explores the marketing strategies of halal and healthy products in increasing consumer purchase intention, with a case study on Mie Muhammadiyah. The research employs a quantitative approach using multiple regression and Structural Equation Modeling (SEM) based on Partial Least Square (PLS) to analyze the impact of promotion mix on consumer purchase intention. The sample comprises 150 respondents selected through purposive sampling based on specific criteria such as age, religion, and preference for halal and healthy products. The results show that elements of the promotion mix, such as advertising, sales promotion, online marketing, and personal selling, significantly influence consumer purchase intention and buying decisions. The conclusion highlights the importance of strengthening the promotion mix strategy to increase awareness and purchase intention toward halal and healthy products, particularly Mie Muhammadiyah. The use of digital platforms in promotions is also considered relevant for expanding market reach and increasing product recognition.